Effect of target distance on controllability for myocontrol. Issue 140 (August 2020) - Borish, Cassie N.; Bertucco, Matteo; Sanger, Terence D.
Highlights: Myocontrol speed is not only affected by accuracy as prescribed by Fitts' law. Speed is also affected by target distance independent of size. Very small distance targets exhibit longer movement times. Small distance movements have higher variability and error, and slower velocity. Abstract: Myocontrol holds great promise because it has the potential to provide flexible and accurate prosthetic control that approaches the quality of normal movement. Speed and accuracy are important factors to consider when applying myoelectric signals to external devices. Fitts's law can be used to assess the speed-accuracy trade-off. We hypothesized that speed is affected not only by accuracy as prescribed by Fitts's law, but also by target distances independent of target size. A total of 12 healthy adult subjects were studied. Subjects controlled the vertical movement of a computer cursor by contracting their dominant first dorsal interosseus muscle to reach targets as quickly as possible. We manipulated twenty-five different target distances in order to obtain five indices of difficulty, as defined by Fitts's law, combined with five target widths. We tested the relationship between movement time and the index of difficulty as predicted by Fitts's law among different combinations of target distance and widths. Results showed a significant linear regression for all conditions, with the exception of a significantly longer movement time than predicted for targets close to the start point. Movements to these targets showed significantly higher relative variance during stabilization, higher overshoot, and lower success. Therefore, we found that with comparable index of difficulty, small distance movements had a higher variability, slower movement, and higher rates of error compared to larger distance movements. Our results are consistent with our hypothesis that low muscle activation required for short distances results in higher variability and low controllability in reaching the target as required by the task demand. Neurophysiological mechanisms underlying the violation of the Fitts's law relationship are discussed. These results have significance for myocontrol applications, and we suggest that such applications require control signals with sufficient recruitment to reduce variability at lower levels of muscle activation.